Role of potassium fertilizer on growth and productivity of ARACHIS HYPOGAEA L. (Latakia University Journal -Biological Sciences Series, 2020)
This research was carried out during 2014-2015 growing seasons to study the role of potassium fertilizer with 5 rates those (0.40.60.80.100)kg/h-1 on some growth  parameters and productivity of Arachis hypogaea L.                                                           A randomized plot design with 3 replication.The result showed the following:-The application rates of potassium fertilizer 40-100 kg/h-1increase  leaves number /plant , flowers number/plant, fresh weight of plant and pod number by plant.-The application of (60.80.100)kg/h-1gave significantly increase in leaves  number , flowers number , fresh weight, pods number/plant compared    with the control.-The application of (80.100)kg/h-1caused significant effect in leave                        number  , flowers number , fresh weight, pods number/plant compared with the rate 40 kg/h-1.